2022-RA-179-ESGO Impact of morbid obesity on the outcomes of type II endometrial cancer: a cohort study. (20th October 2022) - Gaballal, Khaled; Metwally, Islam; Refky, Basel; Refky, Basel; Abdelkhalek, Mohamed; Hamdy, Mohamed
Abstract : Introduction/Background: Obesity has long been associated with endometrial cancer. However, there is a paucity of studies addressing the impact of morbid obesity in type II endometrial cancer on oncologic and surgical outcomes. Methodology: This is a retrospective cohort study on patients who had been surgically treated in Oncology Center Mansoura University (OCMU) for type II endometrial cancer. A total of 62 patients were retrieved in the period from January 2014 till January 2019. The basic epidemiologic and clinicopathologic data were collected and thereafter the patients were arranged on two arms with a cut-off point BMI =40 Kg/m2. The two arms were compared regarding epidemiologic, clinicopathologic criteria and outcomes (surgical and oncological). Results: Sixty-two patients were retrieved: The mean age of the studied population was 64.7 +/- 6.8, and the mean BMI was 36.7 +/- 7.2 Kg/m2. The commonest pathologic type was high grade endometrioid, followed by serous, carcinosarcoma and lastly clear cell.Regarding the surgical outcome there was significantly higher incidence of vaginal margin infiltrated margin among morbid obese patients (.040). However, complications, nodal status, recurrence and survival were comparable as well as disease free survival and overall survival.Para-aortic adenopathy and treatment with preoperative therapy were the only signifcant predictors of DFS. Conclusion: Surgery is feasible with equivalent complications and oncologic outcomes in morbidly obese patients with type II endometrial cancer.